Cuidados de enfermagem às pessoas que convivem com estomias intestinais ou urinárias: revisão narrativa - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Ostomy is a surgical process which consists of a deviation from fecal or urinary elimination, which may be temporary or permanent. This intervention may generate psychological changes and the body image itself, as well as changes in daily life. Thus, nursing must deal with these feelings in order to promote self-care. In view of this, our objective is to identify in scientific productions the nursing care provided to people living with intestinal or urinary stomies. This is a literature review of the narrative type. Data collection was performed using the advanced form in the Latin American and Caribbean Literature in Health Sciences databases. As criteria for inclusion, research articles that respond to the theme, published in Portuguese, English or Spanish, available in full online, between 2009 and 2016, with the guiding question being the guiding question and exclusion criteria, with 24 articles selected as corpus of analysis. Results: the articles showed as results a set of nursing care for people living with intestinal or urinary stomies, presented according to the different processes of stomatal construction, namely: Preoperative, perioperative and postoperative period, and according to the nursing care aimed at the rehabilitation of the ostomate. Conclusion: The development of this study made it possible to verify that nursing care for people with intestinal or urinary stomies, which go through all the periods of stomy manufacture, and scientific knowledge, is necessary to provide support, coping with the new condition of chronicity, thus contributing to the quality of life of the person with the ostomate.
Nursing care for people living with intestinal or urinary ostomies: narrative review
Keywords: Enfermagem; Estomia; Cuidados de enfermagem; Nursing care; Ostomy; Nursing; CNPQ::CIENCIAS DA SAUDE